KETAATAN PEMERINTAH DAERAH BERSAMA DPRD DALAM PEMBENTUKAN RANCANGAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN KUANTAN SINGINGI TAHUN 2023 BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 84 TAHUN 2022 TENTANG PEDOMAN PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH TAHUN ANGGARAN 2023 - Silfania Nigellia; Dodi Haryono; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The preparation of the Local Government Budget based on Regulation of the Ministerof Home Affairs Regulation Number 84 of 2022 Concerning The Guidelines for CompilingThe Local Government Budget for Fiscal Year 2023. However, in its formation in KuantanSingingi Regency the delay in time. Therefore, the purpose of this thesis research is first,mechanism for establishing the draft Local Government Budget for the 2023 KuantanSingingi Regency based on the Minister of Home Affairs Regulation Number 84 of 2022.Second, obstacles encountered in the process. Third, efforts that must be made in overcomingobstacles in the process of forming.This type of research is sociological juridical research. With the research locationtaking place at the Regional People's Legislative Council of Kuantan Singingi Regency andthe Regional Financial and Asset Management Agency of Kuantan Singingi Regency.From the results of the research results it can be concluded. First, mechanism forforming of the draft Local Government Budget of Kuantan Singingi Regency in the 2023 isnot fully in accordance with the Regulation of the Minister of Home Affairs RegulationNumber 84 of 2022. Second, obstacle faced is the internet network and inadequate servers,lack of understanding and weak coordination between regional work units, limited humanresources, and the government's unpreparedness to prepare performance-based budgets.Third, efforts that must be made are making improvements to the Regional Government'sinternet network, increasing human resource development, determining priority scales,synergizing the executive with the legislature in drafting regional regulations on regionalbudgets.Keywords: Compliance, Local Government, Local House of Representative, The Formationof A Draft Local Government Budget